1973
DOI: 10.1002/jsfa.2740240602
|View full text |Cite
|
Sign up to set email alerts
|

Identification and measurement of 2,3‐butanediol in silage

Abstract: 2,3-butanediol was identified in silage extracts using gas chromatography and mass spectrometry. It was present in stacks of untreated and formaldehyde-treated silage in concentrations of 2.4% of the dry matter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1980
1980
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Only a small number of studies have reported 2,3butanediol production in silage. The ensiled materials were grass (Fennessy and Barry 1973;Barry 1975), whole-crop barley (Mathison et al 1981;Nia and Wittenberg 1999) and whole-crop rice (Nishino et al 2007) grown under conventional cultivation and management. The microorganisms associated with diol production have not been elucidated previously.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a small number of studies have reported 2,3butanediol production in silage. The ensiled materials were grass (Fennessy and Barry 1973;Barry 1975), whole-crop barley (Mathison et al 1981;Nia and Wittenberg 1999) and whole-crop rice (Nishino et al 2007) grown under conventional cultivation and management. The microorganisms associated with diol production have not been elucidated previously.…”
Section: Resultsmentioning
confidence: 99%
“…There is evidence that certain silage microorganisms can produce 2,3-butanediol from sugars and organic acids (McDonald et al 1991). However, only a few reports have actually determined the diol even in conventional crop silages (Fennessy and Barry 1973;Barry 1975;Mathison et al 1981;Nia and Wittenberg 1999). Production of 2,3-butanediol might be a distinctive feature of whole-crop rice silage; however, information is lacking and fermentation factors are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The results of Fenton and Mathison (1980), Fennessy and Barry (1973) For personal use only. (Dawson and Hullin 1954a,b;Gabriel et al 1971;Holman et al 1979 …”
Section: Discussionmentioning
confidence: 99%
“…detection at 210 nm. Four calibration standards were prepared by diluting a stock solution 20, 10 n-butyric, and 9.11 isovaleric. The external standard method was used to convert peak areas to concentrations, and duplicate analyses were made.…”
Section: Methodsmentioning
confidence: 99%